2020
DOI: 10.4102/jsava.v91i0.1990
|View full text |Cite
|
Sign up to set email alerts
|

Blood acid–base, haematological and haemostatic effects of hydroxyethyl starch (130/0.4) compared to succinylated gelatin colloid infusions in normovolaemic dogs

Abstract: Synthetic colloids are commonly administered to dogs to treat absolute or relative hypovolaemia. Voluven® (tetrastarch 130/0.4) and Gelofusine® (succinylated gelatin) are available to veterinarians in South Africa. In humans, use of these products has caused acid–base derangements, changes in haematology and impaired haemostasis. We aimed to investigate these effects in healthy normovolaemic dogs. Eight healthy adult beagle dogs underwent a cross-over study, receiving Voluven® or Gelofusine® (10 mL/kg/h for 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Therefore, veterinarians were forced to use alternative licensed options such as gelatins. Only a few reports of the effects on coagulation and renal injury in dogs, and no reports in cats have been published (95,111,(121)(122)(123).…”
Section: Adverse Effects Of Gelatin In Small Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, veterinarians were forced to use alternative licensed options such as gelatins. Only a few reports of the effects on coagulation and renal injury in dogs, and no reports in cats have been published (95,111,(121)(122)(123).…”
Section: Adverse Effects Of Gelatin In Small Animalsmentioning
confidence: 99%
“…In regard to its effects on coagulation, experimental studies have shown that 20 ml/kg of 4% gelatin leads to impaired platelet function (111), but that 10 to 20 ml/kg of 4% gelatin had negligible effects on thromboelastography and plasma coagulation (111,123).…”
Section: Adverse Effects Of Gelatin In Small Animalsmentioning
confidence: 99%
“…Bolus administration of 15 mL/kg of low MW HES to healthy dogs caused PCT prolongation and ROTEM evidence of hypocoagulability beyond dilution (53). However, a slow infusion over 2 h of 10 mL/kg of low MW HES to healthy dogs did not cause any changes in coagulation times or TEG parameters (101). Administration of 10 to 20 mL/kg boluses of high MW HES to healthy horses decreased vWF and FVIII activity (43,44) and caused PCT prolongation beyond the effects of dilution (44).…”
Section: Hydroxyethyl Starchmentioning
confidence: 87%
“…No change in PT and aPTT was found after 5 mL/kg of oxypolygelatin in a second study, compared to baseline (132). Three of the canine studies assessed viscoelastic coagulation (81,101,107), with two studies showing more detrimental effects to the speed and strength of clot formation following HES administration, compared to similar doses of either Haemacell R or succinylated gelatin (81,107).…”
Section: Gelatinmentioning
confidence: 99%